Instituições de microfinanças brasileiras: implicações da lei 11.110 sobre os modelos de negócios sustentáveis - Kochhann, Shaiane Caroline (2017)
Through the lack of access to small-scale financing for low-income populations, microcredit can be referred to as a stimulating policy in terms of social inclusion, allowing individuals to maximize their individual income, constituting small businesses, And thereby restricting poverty and misery in the world. The general objective of this study is to: evidence the influences and developments of Law 11,110 on the operational activity of microcredit institutions operating in Brazil, and with this, to emphasize the economic, social and environmental aspects. The present research is characterized by being of the qualitative type. Thus, seven managers of institutions that deal with microcredit were interviewed. In understanding the logic of sustainable business models, it is important to infer that this new paradigm is about seeking a vision that incorporates three-way governance, which implies dynamic exchanges between government, business and civil society where The environment, the economy and society. It is concluded, therefore, that Law 11.110 affects the performance of the participating institutions, however, in most cases, there are other laws that also directly interfere with the performance of these organizations. Still, with regard to sustainable business models, it is possible to admit that even the financial institutions (interviewed for this study) such as: Development Agency, Cooperative Bank, Development Bank, Central Credit Cooperative, Credit Cooperative, Company Organization Civil Society of Private Interest and the Microentrepreneurial Credit Society, supported mainly by the economic pillar, also have social and environmental actions (even if in a timid manner), with concerns and anxieties regarding social inclusion, and the minimization of Environmental damages that have been occurring daily through the action of man.